Origin of copious recrystallization in cold rolled interstitial free (IF) steels - Quadir, Md Zakaria; Munroe, P. (2013)
Copious recrystallization occurs during the very early stages of annealing in some deformed grains in 85% cold rolled IF steel. This event happens to certain regions in γ oriented grains while the α oriented grains remain unrecrystallized. The orientations of the newly forming grains are near either {111}<123> or {554}<225>, and as a result the intensity at these orientations are high in the recrystallization texture. An investigation by scanning electron microscope (SEM) and electron backscatter diffraction (EBSD) shows that such copious recrystallization event originates from the frequent presence of high crystallographic gradients, at the locations where two set shear bands intersect.